ANALISIS BIAYA STANDAR SEBAGAI KATALISATOR EFISIENSI BIAYA PRODUKSI (Studi pada UMKM Gula Aren Langko) - Muliani, Muliani; Sayuti, Alfian; Murapi, Ikang (STIE PENA, 2022)
Standard costs are costs that are determined in advance before starting the production process. Applying standard costs is useful for improving planning and control, and for facilitating product costing. Standard costs used by companies include standard raw material costs, direct labor standard costs and factory overhead standard costs. The standards set must be prepared at the beginning of the year so that they can be used as a benchmark in the production process which is an important factor for the company for production cost efficiency. The purpose of this study is to analyze using standard costs as a catalyst for production cost efficiency. This research uses descriptive research with a quantitative approach. This study focuses on determining production standards and production cost efficiency with analysis of variance. The object of this research is Langko palm sugar SMEs. The data collection technique used in this study was through interviews and documentation. The analysis used is analysis of variance. The results of research on Langko palm sugar SMEs show that by setting production cost standards it can support production cost efficiency, which means standard costs can be used as a catalyst for production cost efficiency.Keywords: biaya bahan baku, biaya tenaga kerja langsung, biaya overhead pabrik, biayastandar, katalisator biaya produksi, efisiensi biaya